In toto analysis of embryonic organisation reduces tissue diversity to two archetypes requiring specific cadherins - Max Brambach; Jana Wittmann; Marvin Albert; Jérôme Julmi; Robert Bill; Darren Gilmour (Nature Communications)
Abstract Organisms are far greater than the sum of their differentiated cells, as the function of most cell types emerges from their organisation into three-dimensional tissues. Yet, the mechanisms underlying architectural diversity remain poorly understood, partly due to a lack of methods for directly comparing different tissue organisations. Here we establish nuQLOUD, an efficient imaging and computational framework that reduces complex tissues to clouds of nuclear positions, enabling the extraction of cell-type agnostic architectural features. Applying nuQLOUD to whole zebrafish embryos reveals that global tissue diversity can be efficiently reduced to two archetypes, termed ‘amorphous’ and ‘crystalline’. We investigate the role of cadherin cell adhesion molecules in controlling organisational diversity and demonstrate that their expression segregates along tissue-archetypal lines. Targeted perturbations identify N-cadherin as a general driver of the amorphous archetype. This organisation-centric approach provides a way to conceptualise tissue diversification and investigate the underlying mechanisms within a standardised, quantitative framework.